PENGARUH LATIHAN STANDING BARBELL TRICEPS EXTENSION TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA CABANG OLAHRAGA ATLETIK NOMOR LEMPAR LEMBING MAHASISWA PENJASKESREK UNIVERSITAS RIAU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this study is the weak strength of the arms and shoulders of physical education students in the athletic sport of the javelin throw. The title being researched in this study was "The Effect of Standing Barbell Triceps Extension Exercise on Arm and Shoulder Muscle Strength in Athletics with the Jewelery Throwing Number of Penjaskesrek Students Riau University". So that the future goal of students can show even better performance when taking these course grades. The form of this research is (one group pretest-postest design) with a population of 2017 class A Penjaskesrek student at Riau University. The data in this study are the entire population of 28 people. The instrument used in this study was to use the Expanding Dynamometer test, which aims to determine the influence of the Student's Arm and Shoulder Muscle Strength. To test for normality using the Lilifours test at a significant level of 0.05α. Based on the analysis of the normality test of the X data, the Lcount is 0.1348 and Ltable is 0.167, meaning that Lcount <Ltable. while the Y variable produces a Lcount of 0.1452 and an Ltable of 0.167. This means Lhitung <Ltable. then the data is normally distributed. Thus it can be concluded that for the effect between variable x and variable y, the value of t = 6.45 is obtained, then tcount> ttable, namely (6.45)> (1.703), then Ha is accepted, in other words there is a significant effect on the effect of standing exercise. Barbell Against Arm and Shoulder muscle strength in Athletic Sports with Javelin Throwing Student of Penjaskesrek, Riau University.Key Words: Standing Barbell Exercise, Arm and Shoulder Muscle Strength